Diminished physical function in older HIV-infected adults in the Southeastern U.S. despite successful antiretroviral therapy. - Audrey L Khoury; Miriam C Morey; Tammy C Wong; Donna Lynn McNeil; Barlett Humphries; Katherine Frankey; Carl F Pieper; Charles B Hicks; Kim Huffman; Mehri S McKellar (PLoS ONE)
Background As antiretroviral therapy efficacy improves, HIV is gradually being recognized more as a chronic disease within the aging HIV-infected population. While these individuals are surviving into old age, they may, however, be experiencing "accelerated aging" with greater declines in physical function than that observed among comparably matched individuals free of HIV. This decline is not well understood and it remains unclear if physical decline correlates with the degree of immunosuppression based on CD4 lymphocyte nadir. Methods In a cross-sectional study of accelerated aging in the older HIV-infected population on antiretroviral therapy (ART), physical performance evaluations were completed on a cohort of 107 HIV-infected subjects, age 50 years or older (with no HIV-1 RNA >200 copies/mL in the prior 12 months), and compared to reference ranges for age- and gender-matched HIV-uninfected persons. Physical performance testing consisted of four validated assessments: the 2.4-meter walk, 30-second chair stand, grip strength and 6-minute walk test. Results When compared to age- and gender-matched HIV-uninfected reference controls, older HIV-infected persons had diminished physical function. No correlation was found between physical function and degree of immunosuppression as determined by pre-ART CD4 nadir. Conclusions Despite improved survival, HIV-infected adults on suppressive ART have diminished physical function compared to HIV-uninfected persons. The degree of HIV-associated immunosuppression does not correlate with the observed degree of physical function decline in older HIV-infected persons, suggesting the decline is mediated by other mechanisms.